Bud initiation of azaleas: Preliminary studies on flower development indicate frequent removal of branch terminals will produce abundant flowering - H Kohl; R Sciaroni (California Agriculture, 1956)
Azalea plants are forced to bloom in large quantities for the retail market from Christmas through Easter. To achieve an abundance of flowers, even flowering, and rapid forcing, the grower must remove branch terminals—pinch— frequently to cause profuse branching which is a foreunner to abundant flowering. To make the plants flower rapidly they must be given a low temperature treatment after the buds are developed and before forcing begins. For an even flowering all buds must be initiated and developed simultaneously.